Chronic hypertension in pregnancy stratified by first‐trimester blood pressure control and adverse perinatal outcomes: A prospective observational study. (17th March 2021) - Dumitrascu‐Biris, Dan; Nzelu, Diane; Dassios, Theodore; Nicolaides, Kypros; Kametas, Nikos A.
Abstract: Introduction: The aim of this study was to assess perinatal outcomes in women with chronic hypertension (CH) stratified into four groups according to their blood pressure (BP) control in the first trimester of pregnancy. Material and methods: This was a prospective cohort study between January 2011 and June 2017, based in a university hospital in London, UK. The population consisted of four groups: group 1 included women without history of CH, presenting in the first trimester with BP >140/90 mmHg (n = 100). Groups 2‐4 had prepregnancy CH; group 2 had BP <140/90 mmHg without antihypertensives (n = 234), group 3 had BP <140/90 mmHg with antihypertensives (n = 272), and group 4 had BP ≥140/90 mmHg despite antihypertensives (n = 194). The main outcome measures were: fetal growth restriction, admission to neonatal (NNU) or neonatal intensive care unit (NICU) for ≥2 days, composite neonatal morbidity, and composite serious adverse neonatal outcome. Outcomes were collected from the hospital databases and for up to 6 weeks postnatally. Differences between groups were assessed using chi‐squared test and multivariate logistic regression was used to assess the independent contribution of the four groups to the prediction of pertinent outcomes, after controlling for maternal characteristics. Results: There was a higher incidence of fetal growth restriction in groups 3 (17.6%) and 4 (18.2%), compared with groups 1 (10.0%) and 2 (11.1%) ( P  = .04). There were more admissions to the NNU for ≥2 days in groups 3 (23.2%) and 4 (25.0%), compared with groups 1 (17.0%) and 2 (13.2%) ( P  = .008); and more admissions to NICU for ≥2 days in groups 3 (9.2%) and 4 (9.4%), compared with groups 1 (3.0%) and 2 (3.4%) ( P  = .01). Composite neonatal morbidity was higher in groups 3 (22.4%) and 4 (21.4%), compared with groups 1 (17.0%) and 2 (11.5%) ( P  = .009). Composite serious adverse postnatal outcome was higher in groups 3 (3.3%) and 4 (4.2%), compared with groups 1 (1.0%) and 2 (0.9%) but the difference did not reach statistical significance ( P  = .09). These results were also observed when values were adjusted for maternal characteristics. Conclusions: In CH adverse perinatal outcomes are worse in women who are known to have CH and need antihypertensives in the first trimester of pregnancy. Women with newly diagnosed CH in the first trimester have similar outcomes to those with known CH who have antihypertensive treatment discontinued.